Understanding factors of ambulance delay and crash to enhance ambulance efficiency: an integrative literature review - Ketut Shri Satya Wiwekananda; Rizqiko Pandai Hamukti; Ketut Shri Satya Yogananda; Kadek Egadia Calisto; Prattama Santoso Utomo (Journal of Community Empowerment for Health, 2020)
Trauma is one of the major causes of deaths worldwide. The referral time of trauma patients to the trauma center is a vital determinant of traumatic injury patients’ survival. Ambulance delays and crashes are the major causes of delay of patient transportation to the hospital. This review was conducted to find the main factors that cause ambulance crashes and ambulance delays; and discuss the correlation of both factors. Hence, the authors might suggest an appropriate solution to minimize ambulance delay and crash incidents. This integrative literature review applied the PRISMA-P protocol to ensure a robust literature search. A total of nine databases and publishers (i.e., PubMed, Scopus, ScienceDirect, ASCE Library, Clinical Key, EBSCO, Cambridge, Taylor & Francis, and ProQuest) were searched using relevant keywords to obtain studies on ambulance delays and ambulance crashes. The literature search retrieved 620 studies to be screened based on the exclusion-inclusion criteria which finally resulted in the 12 studies included in the review. The researchers conducted a risk of bias assessment using Joanna Briggs Institute's critical appraisal tools. Data from the included studies were then extracted and analyzed using descriptive statistics to identify the factors affecting ambulance delays and crashes. After conducting an integrative literature review, the main factor that causes ambulance delays is traffic congestion. Meanwhile, the main factor causing ambulance crashes is intersection. Traffic congestion often occurs especially at intersections. The authors concluded that, intersections have a significant effect on ambulance delays and also ambulance crashes. To overcome this problem, the authors suggest to make an additional ambulance caution signal lamp on all congested intersections.